Tindak Tutur Ilokusi pada Video Pidato Kemenangan Prabowo-Gibran di Channel YouTube CNBC Indonesia - Riri Kumalasari; Leni Novita Sari; Silfira Catur Januarista; Tommi Yuniawan; Qurrota Ayu Neina (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
. This study analyzes the illocutionary speech acts in Prabowo-Gibran's victory speech on YouTube CNBC Indonesia. Using a qualitative descriptive approach, this study examines the speech utterances and identifies the types of illocutionary speech acts used. The results reveal five types of illocutionary speech acts: assertive, directive, declarative, commissive, and expressive. In the speech, there are a variety of utterances that include telling, boasting, begging, forbidding, promising, and thanking. The implication of this research is to broaden the understanding of language use in political communication, as well as to explore the communication strategies used by political leaders in influencing public opinion. This research makes an important contribution to the understanding of modern political dynamics and the interaction between political leaders and the public through digital media.